PERAN STAKEHOLDER DALAM PENGELOLAAN HUTAN MANGROVE LUWUK TIMUR KABUPATEN BANGGAI PROVINSI SULAWESI TENGAH - Ummu Kalsum; Ris Hadi Purwanto; Lies Rahayu WF; Sumardi Sumardi (Program Studi Manajemen Hutan, Pascasarjana Universitas Pattimura, 2022)
The mangrove forest in East Luwuk has been damaged. resulting in a reduction in area. The parties involved in ensuring that you are not optimal so that the condition of the mangrove remains degraded. This research was conducted to identify the stakeholders involved in the management, analyze the role of stakeholders and describe the relationship between stakeholders in mangrove forest management. The research was conducted in the East Luwuk mangrove forest, Banggai Regency, Central Sulawesi Province. The results showed that the Key Players had not made a mangrove forest management plan which resulted in a lack of synergy in the activities carried out by the managers. In order for mangroves to be sustainable, it is necessary to increase the role of the community which was originally only a subject to become a key player through community empowerment activities. Provincial and District Governments as well as Universities need to improve from Crowd to Context Setters who have a big influence in policy making. It is necessary to form a Coordination Team for Mangrove Forest Management Strategy at the provincial and district levels to synergize policies and programs for managing mangrove ecosystems. Empowerment activities need to be carried out intensively to encourage a change in the role of mangrove management.